1991
DOI: 10.1073/pnas.88.19.8606
|View full text |Cite
|
Sign up to set email alerts
|

A single base deletion in the Tfm androgen receptor gene creates a short-lived messenger RNA that directs internal translation initiation.

Abstract: Testosterone-resistant male mice hemizygous for the X-chromosome-linked mutant gene Tfm express detectable but severely reduced levels of androgen receptor mRNA, amounting to about 10% of the level found in normal male littermates. No structural abnormality could be identied in the coding region of the messenger by a series of RNaseprotection assays. However, cell-free translation of RNAs transcribed in vitro from enzymatically ampfied overlapping segments of exon 1 revealed a truncated receptor protein and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 43 publications
(47 reference statements)
2
57
0
2
Order By: Relevance
“…In both prokaryotes and eukaryotes nonsense mutations in a gene can reduce the abundance of the mRNA transcribed from that gene (Morse and Yanofsky 1969;Losson and Lacroute 1979;Maquat et al 1981;Pelsy and Lacroute 1984;Baumann et al 1985;Nilsson et al 1987;Daar and Maquat 1988;Urlaub et al 1989;Cheng et al 1990;Gozalbo and Hohmann 1990;Barker and Beamon 1991;Gaspar et al 1991;Leeds et al 1991;Baserga and Benz 1992;Lim et al 1992;Cheng and Maquat 1993). Results of this study and others indicate that in S. cerevisiae this nonsense-mediated effect can be attributed to cytoplasmic events that are concurrent with mRNA translation.…”
Section: Nonsense Mutations Accelerate Cytoplasmic Mrna Decay In Yeastmentioning
confidence: 59%
“…In both prokaryotes and eukaryotes nonsense mutations in a gene can reduce the abundance of the mRNA transcribed from that gene (Morse and Yanofsky 1969;Losson and Lacroute 1979;Maquat et al 1981;Pelsy and Lacroute 1984;Baumann et al 1985;Nilsson et al 1987;Daar and Maquat 1988;Urlaub et al 1989;Cheng et al 1990;Gozalbo and Hohmann 1990;Barker and Beamon 1991;Gaspar et al 1991;Leeds et al 1991;Baserga and Benz 1992;Lim et al 1992;Cheng and Maquat 1993). Results of this study and others indicate that in S. cerevisiae this nonsense-mediated effect can be attributed to cytoplasmic events that are concurrent with mRNA translation.…”
Section: Nonsense Mutations Accelerate Cytoplasmic Mrna Decay In Yeastmentioning
confidence: 59%
“…Three groups have reported that androgen resistance in the Tfm mouse is caused by a frame shift at amino acid position 371 followed by a premature termination of the AR protein occurring 42 amino acids later (27)(28)(29). Those studies suggested that reinitiation of AR protein synthesis at a methionine downstream of the premature stop codon might account for residual [3H ]dihydrotestosterone binding found in the Tfm mouse.…”
Section: Discussionmentioning
confidence: 99%
“…The 5Ј primer contains a T3 RNA polymerase recognition site upstream of an ATG initiation codon in frame with RLIP1 (CGAATTAACCCTCACTA-AAGAAGGATGGAGATCCTAGAACTAGTCGG) (12). The 3Ј primer is downstream of the stop codon of the amplified fragment (GTAAAAC-* This work was supported in part by grants from Association pour la Recherche contre le Cancer (ARC), Ligue Nationale contre le Cancer, Ligue contre le Cancer (Comité de Paris), and Groupement de Recherche et d'Etudes sur les Génomes.…”
Section: Methodsunclassified